plataforma colaborativa para organização e gestão de conferências - Luís Miguel Rodrigues Oliveira (2014)
The organization and management of scientific events such as conferences, seminars or colloquia are normally a laborious and complex process. To ensure the smooth organization of a conference from the outset and ensure its success, have been created in recent years information systems that allow simplify their management, performing many of the needed tasks automatically. Cid Conference is an information system created in 2005 by the company Mercatura - Informação e Tecnologia, which has been widely used in supporting the organization and management of scientific conferences with dimensions and levels of complexity. This thesis proposes that after a thorough analysis of the state of the art of similar systems and analyzing the main functionalities required by an application of this nature, to identify and add new functionality to the system Cid Conference, allowing this platform distinguishes itself positively in relation to remaining on the market. The objective of this thesis is to implement features that bring added value to the platform Cid Conference, having identified two critical functionalities. First, a module of the conference program, with features that allow the user to automatically generate a program with sessions that he considers most interesting. The second functionality is implemented in the introduction of a small social network in the application using the patterns that have previously been identified as being most relevant. The purpose of this feature is to bring the benefits of a social network for a conference, actively promoting the interaction between conference participants. The final product not only contributed to improving the platform Cid Conference, making more complete platform but also decisively changed the way users participating in a conference, allowing a greater interaction throughout the process.